PERAN ETIKA DAN PROFESI KEGURUAN DALAM MEMBANGUN KARAKTER SEBAGAI CALON GURU - Nihaya, Musdalifah (IQRA : JURNAL MAGISTER PENDIDIKAN ISLAM, 2024)
Professional teachers not only rely on material but also on moral quality, character and upholding the values of a professional code of ethics. The main aim of this research is to shape the character of students in preparing them as future teachers according to the demands of the times. This research approach uses library research. Researchers collect data by reading, investigating, and analyzing publications and articles necessary for research. The main result to be achieved is the role of ethics and the teaching profession in building student character as prospective teachers. The role of ethics and the teaching profession in building students' potential character values is very important, as prospective teachers they must be able to explore noble moral values so that they can become role models for the school and the environment in the future.